2015
DOI: 10.1590/1516-635x1703387-394
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Eggshell Temperatures Between Embryonic Day 10 and 18 on Broiler Performance and Susceptibility to Ascites

Abstract: The aim of the current study was to determine the effects of low (33.3-36.7 ˚C), control (37.8-38.2 ˚C) and high (38.9-40.0 ˚C) eggshell temperatures (ESTs) between days 10-18 of incubation on broiler performance and susceptibility to ascites. The effects of different ESTs on hatchling weight were significant. The highest residual yolk sac weight (7.7 g) and relative yolk sac weight (18.7%) were observed in high EST group, whereas the highest yolk-free body weight (36.22 g) was obtained in the control group. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
3
12
2
3
Order By: Relevance
“…The reduction in the RBCs, PCV, Hb and WBCs in the chronic group could be attributed to the adverse effects of high incubation temperature on the embryos. These results disagree with those of Ipek et al (2015), who found that the higher PCV and RBC values were obtained in the high incubation group as compared to the low incubation temperature and control groups, while the Hb level was lower in the control group than in the high and low incubation temperature groups.…”
Section: Haematological Parameters Leukocytes Differential Percentagcontrasting
confidence: 99%
See 1 more Smart Citation
“…The reduction in the RBCs, PCV, Hb and WBCs in the chronic group could be attributed to the adverse effects of high incubation temperature on the embryos. These results disagree with those of Ipek et al (2015), who found that the higher PCV and RBC values were obtained in the high incubation group as compared to the low incubation temperature and control groups, while the Hb level was lower in the control group than in the high and low incubation temperature groups.…”
Section: Haematological Parameters Leukocytes Differential Percentagcontrasting
confidence: 99%
“…The increased cloacal temperature in the chronic temperature can indicate embryo response to high incubation temperature. These results Ipek et al (2015) who found that the cloacal temperature was significantly increased to 40.5 °C in chicks from the high incubation temperature group (38.9-40.0 °C) in comparison with low incubation temperature group (33.3-36.7 °C) and control one (37.8-38.2 °C ), in which the cloacal temperature was 38.7 and 39.4 °C, respectively. Treating animals with 500 and 1000 mg BP/kg diet significantly (P ≤ 0.05) increased T3 and T4 plasma concentrations; while in group treated with 1500 mg/kg diet T3 did not differ and T4 was significantly lower from the control group.…”
Section: Thyroid Hormone Concentrations and Cloacal Temperature Of Nesupporting
confidence: 62%
“…ET is influenced by embryonic heat production, and changes in ET have been shown to be associated with changes in hatchling quality and posthatch broiler performance ( Molenaar et al., 2011 , Ipek et al., 2015 ). Increases in ET beyond standard levels (ET between 38.9 and 40.0°C) during the second half of incubation have resulted in a decreased hatchability and hatchling weight and increased residual yolk sac weight in early posthatch broilers ( Ipek et al., 2015 ). At the same time period of incubation, ET at 38.9°C or greater also has resulted in a higher FCR in 6-wk-old broiler chickens and has led to increases in the incidences of metabolic diseases such as ascites ( Molenaar et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an increase in ET is associated with decreases in relative embryo weight and yolk-free BW ( Ipek et al., 2014 ); a lower ET is associated with increased hatchling BW and chick quality ( Zhai et al., 2011 ). In comparison with birds having an ET between 37.8 and 38.2°C, the feed conversion ratio ( FCR ) of broilers that experienced a low (33.3-36.7°C) or high (38.9-40.0°C) ET has been shown to be higher between wk 4 and 6 after hatching ( Ipek et al., 2015 ). Various vitamin D 3 sources can modulate metabolism and have a potential to subsequently affect ET, which may positively affect broiler performance.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of eggs' Eggshell's temperature was done twice on the different sides, then the data of measurement was taken its mean. The use of infrared thermometer referred to Ipek et al (2015).…”
Section: Eggshell Temperaturementioning
confidence: 99%